Improving Achievement and Attitudes towards Mathematics Using Problem-Based Learning Setting Team Accelerated Instruction - Anggoro Eko Yuni Cahyono (JME (Journal of Mathematics Education), 2019)
Learning achievement and attitude towards mathematics are two of the indicators of student success in learning mathematics. Problems related to these two things that occur in classrooms where the author teaches encourage the author to make improvements in learning through a classroom action research to improve student achievement and attitudes toward mathematics. Classroom action research is carried out by applying Problem-Based Learning (PBL) with Team Accelerated Instruction (TAI) arrangements. Data were collected using two types of instruments, namely mathematics achievement test, and students' attitude toward mathematics questionnaire. The results showed that the average attitude of students towards mathematics there were 81% of students had good attitude categories to the top (59% good categories and 22% of very good categories), student achievement as much as 87.50% had been completed with an average student completeness is 81.75 while the implementation of learning activities has exceeded the specified target that is equal to 92.11% has been implemented. It can be concluded that the application of the PBL setting TAI model has succeeded in improving student achievement and student attitudes towards mathematics.